Ectopic Fat Depots and Left Ventricular Function in Nondiabetic Men With Nonalcoholic Fatty Liver Disease. (January 2015) - Granér, Marit; Nyman, Kristofer; Siren, Reijo; Pentikäinen, Markku O.; Lundbom, Jesper; Hakkarainen, Antti; Lauerma, Kirsi; Lundbom, Nina; Nieminen, Markku S.; Taskinen, Marja-Riitta
<x xml:space="preserve">Abstract</x> Background— Nonalcoholic fatty liver disease has emerged as a novel cardiovascular risk factor. The aim of the study was to assess the effect of different ectopic fat depots on left ventricular (LV) function in subjects with nonalcoholic fatty liver disease. Methods and Results— Myocardial and hepatic triglyceride contents were measured with 1.5 T magnetic resonance spectroscopy and LV function, visceral adipose tissue (VAT) and subcutaneous adipose tissue, epicardial and pericardial fat by MRI in 75 nondiabetic men. Subjects were stratified by hepatic triglyceride content into low, moderate, and high liver fat groups. Myocardial triglyceride, epicardial and pericardial fat, VAT, and subcutaneous adipose tissue increased stepwise from low to high liver fat group. Parameters of LV diastolic function showed a stepwise decrease over tertiles of liver fat and VAT, and they were inversely correlated with hepatic triglyceride, VAT, and VAT/subcutaneous adipose tissue ratio. In multivariable analyses, hepatic triglyceride and VAT were independent predictors of LV diastolic function, whereas myocardial triglyceride was not associated with measures of diastolic function. Conclusions— Myocardial triglyceride, epicardial and pericardial fat increased with increasing amount of liver fat and VAT. Hepatic steatosis and VAT associated with significant changes in LV structure and function. The association of LV diastolic function with hepatic triglyceride and VAT may be because of toxic systemic effects. The effects of myocardial triglyceride on LV structure and function seem to be more complex than previously thought and merit further study.